Unveiling the bioactive potential of Scabiosa rotata M. Bieb fruits: a landmark study on cytotoxic, antioxidant, and antibacterial activities through liquid chromatography-mass spectrometry profiling and molecular docking - Yildirim, Aybeniz; Celep, Inci Kurt; Gul, Abdulkadir; Eter, Ozge Soylu; Bagci, Eyup (Oxford Univ Press, 2025)
The aim of this study was to investigate the antioxidant, cytotoxic, and antibacterial activities of ethanol extract (SRE) and its hexane (SRH), chloroform (SRC), ethyl acetate (SREA), and aqueous ethanol (SRAE) sub-extracts obtained from the fruits of Scabiosa rotata M. Bieb. Molecular docking studies were also performed to evaluate the interactions of the most active sub-extract with the human mitochondrial ABC transporter (ABCB10) protein, plays an important role in cellular oxidative stress regulation and mitochondrial function. Total phenolic (TPC) and flavonoid (TFC) contents and antioxidant radical scavenging activities (1, 1-diphenyl-2-picryl hydrazyl [DPPH] and 3-ethylbenzothiazoline-6 sulfonic acid [ABTS]) of all extracts were determined. Cytotoxic activity was evaluated on different cell lines, such as HepG2 (liver cancer), MCF-7 (breast cancer), and HeLa (cervical cancer) cells. Antibacterial activity was tested against Escherichia coli, Pseudomonas aeruginosa, Enterococcus faecalis, and Staphylococcus aureus. SREA showed the best antioxidant activity with IC50 values of 54.20 mu g/ml and 48.56 mu g/ml for DPPH and ABTS, respectively, and also had high TPC (499.06 mg GA/g) and TFC (327.45 mg QE/g). Furthermore, SREA showed significant cytotoxicity comparable to cisplatin with IC50 values of 51.29, 51.41, and 52.89 mu g/ml for HepG2, MCF-7, and HeLa cells, respectively. However, none of the extracts showed antibacterial activity. The analysis using liquid chromatography-mass spectrometry (LC/MS-MS) on SREA found that the main phenolic compounds are chlorogenic acid, hesperidin, quinic acid, and isoorientin. Molecular docking of the major compounds showed that chlorogenic acid (2.21 mM) exhibited the strongest binding affinity, followed by hesperidin (5.83 mM), quinic acid (8.86 mM), and isoorientin (13 mM). These findings indicate the potential of SREA to be used as a natural antioxidant and anticancer agent.
Keywords: Scabiosa rotata; natural anticancer agent; antioxidant activity; ABCB10 protein; LC-MS/MS